Evaluasi Kritis Perusahaan Listrik Negara (Persero) terhadap Kebijakan Subsidi Listrik - Martha Carolina (Pusat Kajian Anggaran, 2021)
This research has objectives to explore the effect of electricity subsidies on the financial performance of The State Electricity Company (PT PLN Persero). This research uses the associative descriptive research method. The secondary data used in this study are quantitative, namely the financial statements of PT PLN (Persero) for 2010-2020. The results obtained that the financial performance of PT PLN (Persero) is highly dependent on government subsidies. Based on the results of the spearman rank correlation test, there is a relationship between the cash ratio and the solvency ratio with electricity subsidies. Also, there is no relationship between profitability ratios and liquidity ratios with electricity subsidies.